Intersubjectivity and the Emergence of Words - Terrace, Herbert S.; Bigelow, Ann E.; Beebe, Beatrice (Frontiers in Psychology, 2022)
Intersubjectivity refers to two non-verbal intersubjective relations infants experience during their first year that are precursors to the emergence of words. Trevarthen, a pioneer in the study of intersubjectivity, referred to those relations as primary and secondary intersubjectivity. The former, a dyadic coordination between the infant and her caregiver, begins at birth. The latter, a triadic coordination that develops around 9 months, allows the infant and a caregiver to share attention to particular features of the environment. Secondary intersubjectivity is crucial for an infant’s ability to begin to produce words, at around 12 months. Much research on the social and cognitive origins of language has focused on secondary intersubjectivity. That is unfortunate because it neglects the fact that secondary intersubjectivity and the emergence of words are built on a foundation of primary intersubjectivity. It also ignores the evolutionary origins of intersubjectivity and its uniquely human status. That unique status explains why only humans learn words. This article seeks to address these issues by relating the literature on primary intersubjectivity, particularly research on bi-directional and contingent communication between infants and mothers, to joint attention and ultimately to words. In that context, we also discuss Hrdy’s hypothesis about the influence of alloparents on the evolution of intersubjectivity.